SPIRIT TA’AWUN DALAM STRATEGI PEMASARAN PEDAGANG PASAR BESAR KOTA PALANGKA RAYA - Novi Angga Safitri (LP2M IAIN Palangka Raya, 2021)
In the practice of Ta'awun, the traders of Pasar Besar at Palangka Raya City performed it by helping each other in providing and selling the goods needed by buyers, as well as to other fellow traders. However, there were still some traders who did not help each other with other traders because they thought there was business competition. This study attempted to determine the form and constraints of the implementation of Ta'awun spirit of the traders’ marketing strategy. The form of implementation of the Ta'awun Spirit in Pasar Besar traders at Palangka Raya City was to apply the P4 concept, namely: Product, Price, Place, and Promotion. The obstacles to the implementation of the Ta'awun Spirit of Pasar Besar traders at Palangka Raya City were divided into two, namely: (a) from the traders’ perspective, the problem was that sometimes there were traders who did not give their wares to other traders for resale. In addition, in terms of price sometimes it was not in accordance with the agreement. When other traders want to sell their goods. They sold goods to fellow traders with a price higher than the market price. (b) From the buyers’ side, when the desired product has been provided, and the item was already existed, the buyers suddenly cancelled without unclear reasons and sometimes impatient, so that they just left when the item is being looked for.